1982
DOI: 10.1007/bf00238107
|View full text |Cite
|
Sign up to set email alerts
|

Arm trajectory formation in monkeys

Abstract: The formation of forearm trajectories of moderate velocities (0.3-1.3 rad/s) was studied in monkeys performing a simple visuomotor task. The experiments were designed to test the hypothesis that the transition from one position to another is subserved by a rapid shift to a final equilibrium of forces in agonist and antagonist muscles. This idea is attractive because it suggests the possibility that in simple movements the trajectory is determined by the inherent inertial and viscoelastic properties of the limb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
72
2

Year Published

1983
1983
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 313 publications
(78 citation statements)
references
References 15 publications
4
72
2
Order By: Relevance
“…This idea appears somewhat consistent with equilibrium point hypotheses, which suggest that central representation of aimed movements is best described as a series of programmed postures (Bizzi et al 1982;Feldman 1966;Feldman et al 1998;Jaric et al 1994;Latash and Gottlieb 1990;Latash and Gutman 1993;Bizzi 1978, 1979). Jaric et al (1992Jaric et al ( , 1994 provided evidence for such positional control through a learning study in which different groups of subjects practiced single joint movements from several start locations to either a fixed position in space or a fixed distance from start location.…”
Section: Specification Of Movement Extentsupporting
confidence: 73%
See 1 more Smart Citation
“…This idea appears somewhat consistent with equilibrium point hypotheses, which suggest that central representation of aimed movements is best described as a series of programmed postures (Bizzi et al 1982;Feldman 1966;Feldman et al 1998;Jaric et al 1994;Latash and Gottlieb 1990;Latash and Gutman 1993;Bizzi 1978, 1979). Jaric et al (1992Jaric et al ( , 1994 provided evidence for such positional control through a learning study in which different groups of subjects practiced single joint movements from several start locations to either a fixed position in space or a fixed distance from start location.…”
Section: Specification Of Movement Extentsupporting
confidence: 73%
“…In contrast to this hypothesis, a separate line of research has supported the idea that limb configurations, corresponding to final hand position, best reflect the central representation of aimed movements (Bizzi et al 1982;Feldman 1966;Feldman et al 1998;Jaric et al 1994;Latash and Gottlieb 1990;Latash and Gutman 1993;Bizzi 1978, 1979). The equilibrium point hypothesis, developed by Feldman (1966) and originally supported by an elegant series of experiments in deafferented monkeys Bizzi 1978, 1979), proposes that the CNS controls movements by modifying the length-tension characteristics of muscles such that the equilibrium position for a set of agonist/antagonist muscles corresponds to a desired limb configuration.…”
Section: Introductionmentioning
confidence: 99%
“…The planned movement was given as an input signal consisting of three EP's: the starting angle, an angle midway, and the planned angle at the endpoint. This double-step EP-trajectory was similar to the trajectory used by Kistemaker et al (2006) and chosen this way since it has been indicated that EP does not shift instantaneously from starting to endpoint (Bizzi et al 1982). For simplicity, feedback gains were kept at constant values of −0.4 m −1 for muscle fiber length and −0.15 s/m for muscle fiber contraction velocity in all simulations described in this study.…”
Section: Modelsmentioning
confidence: 99%
“…In our study, we considered the first and second levels, in that we addressed 3-dimensional goal-directed reaching movements, characterized by a single target position. By leaving out the question of how such high-level control is then translated into muscle synergies and the control of posture and muscle tone, we follow the observation that: electrical stimulation of the brain motor area elicits reaching movements in primates (Graziano et al 2002(Graziano et al , 2005 and leg movements in frogs (Bizzi et al 1982). Interestingly, all of these movements converge to the same position in extrinsic space independently from the initial posture.…”
Section: Assumptions Of the Modelmentioning
confidence: 93%